1982
DOI: 10.1523/jneurosci.02-04-00503.1982
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and kinetics of neurite extension from sympathetic neurons in culture are age dependent

Abstract: Long term (2- to 3-week) cultures of superior cervical ganglia (SCG) were established from rats and rat embryos ranging in age from 15 days of gestation (E15) to 279 days postnatal (P279). Cultures were grown on a collagen substratum and fed a serum-containing medium with added nerve growth factor. Radial outgrowth of neurites was measured as a function of time for up to 2 to 3 weeks. Computer-aided analysis generated estimates of onset time, initial rate, and subsequent changes in the rate of growth of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 26 publications
3
22
1
Order By: Relevance
“…Such factors were probably present in our complex medium, which contained embryo extract. Indeed, our estimate of the initial rate of neurite outgrowth, ~40 gm/h, is comparable to rates observed in previous studies of cultured ciliary and sympathetic ganglion neurons (Collins and Dawson, 1982;Bray, 1973;Argiro and Johnson, 1982;Argiro et al, 1984). Unfortunately, nothing is known about factors that might regulate the long term maintenance of neurites in vitro.…”
Section: MVsupporting
confidence: 86%
“…Such factors were probably present in our complex medium, which contained embryo extract. Indeed, our estimate of the initial rate of neurite outgrowth, ~40 gm/h, is comparable to rates observed in previous studies of cultured ciliary and sympathetic ganglion neurons (Collins and Dawson, 1982;Bray, 1973;Argiro and Johnson, 1982;Argiro et al, 1984). Unfortunately, nothing is known about factors that might regulate the long term maintenance of neurites in vitro.…”
Section: MVsupporting
confidence: 86%
“…Indeed, in a serum-free culture of aged rat sympathetic ganglion cells [22,23] in which the growth of nonneuronal cells was inhibited and thus neurites were clearly seen, the growth of neurites from aged animals was significantly shorter in comparison with that from newborn and young animals, even in the presence of a full dose of nerve growth factor [23]. A similar reduction in neurite re generation due to aging has also been found in serum-rich culture conditions [1,44],…”
Section: Discussionmentioning
confidence: 81%
“…It has previously been shown that neurite extensions from sympathetic neurons in culture are age dependent [Argiro and Johnson, 1982]. In those investigations the onset time and the initial rate of growth on neurites from DRG from prenatal, perinatal and postnatal rats were determined.…”
Section: Discussionmentioning
confidence: 99%